2017
DOI: 10.1111/cid.12484
|View full text |Cite
|
Sign up to set email alerts
|

Implant‐supported mandibular removable partial dentures: Functional, clinical and radiographical parameters in relation to implant position

Abstract: Implant support to a Kennedy class I RPD significantly improves masticatory function, regardless of implant position. No major clinical problems were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Food comminution and homogenization index were improved after conversion from conventional RPD to IARPD (Campos, Goncalves, & Rodrigues Garcia, ; Goncalves, Campos, Goncalves, de Moraes, and Rodrigues Garcia, ; Jensen et al, ). Campos et al reported that the number of masticatory cycles before swallowing was not significantly different after conversion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Food comminution and homogenization index were improved after conversion from conventional RPD to IARPD (Campos, Goncalves, & Rodrigues Garcia, ; Goncalves, Campos, Goncalves, de Moraes, and Rodrigues Garcia, ; Jensen et al, ). Campos et al reported that the number of masticatory cycles before swallowing was not significantly different after conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies analyzed the survival rate of implants after loading for at least 6 months (Bahrami & Alsharbaty, ) (Bae et al, ; Disha et al, ; Jensen, Meijer, Raghoebar, Kerdijk, & Cune, ; Jensen et al, ; Ortiz‐Puigpelat, Gargallo‐Albiol, Hernandez‐Alfaro, & Cabratosa‐Termes, ; Threeburuth et al, ; Wismeijer et al, ) (Table ). In most studies (6/8), a single implant was placed in each distal extension edentulous area.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations